ANALISIS STRATEGI KOMUNIKASI DALAM PENINGKATAN KUALITAS HASIL LAYANAN DI NISSAN PURI INDAH (Studi Kasus Pengunaan Email sebagai Hot Alert dalam Menentukan Kebijakan Pasca Guna Jasa) - Hendrawan Hendrawan (MediaKom : Jurnal Ilmiah Komunikasi, 2017)
This study focuses on communications strategy post-service-follow-up which is comprehensive with the tools of new media that is able to read quickly and accurately what the customers need and also to determine the level of quality owned by a company. The aims of this research are to find out how the communication strategy is built to improve the quality the results of the service and to know how the email acts as hot alert to determine policy post-service-follow-up. This research is carried out by the case study method and the data gathered from in-depth interviews, observation and document company. The result is built to improve the quality of the service is to make every customer's voice sent directly through email serves as hot alert to the relevant officials immediately responded with improvement activities so that the problem can be quickly resolved. The quality of service can also be increased. The result is made in the form of new measures to ensure that similar events will not be repeated.Keywords: post-service-follow-up, email, hot alert